Upaya Meningkatkan Kepedulian Masyarakat Terhadap Lingkungan Melalui Pembuatan Bak Sampah dari Bambu - Lalu Ahmad Didik Meiliyadi; Juliana Marsena (Research Lecturer Community-Mathematics Education Department, State Islamic University of Mataram, 2022)
Community service has been carried out to Aik Prapa village to increase community awareness of luingkungan through training on making garbage bins from bamboo. In general, service activities are carried out in 4 stages, namely preparation, socialization, implementation and evaluation as well as reflection. Service activities have a positive impact on the community. However, there is a criterion that has a poor response, namely the training time. The training time given is too little so there are still some variations that cannot be discussed. But in general, the implementation of devotion is quite good. This is shown by the high level of enthusiasm of students during coaching. The response of students to the speaker was also good, which was shown by the evaluation of the questionnaire which was included in the excellent category. In addition, the motivation of students during training is also included in the excellent category.